The privacy of the psychical - Gilead, Amihud. (Value Inquiry Book Series, 2011)
This book argues that the irreducible singularity of each person as a psychical subject implies the privacy of the psychical and that of experience, and yet the private accessibility of each person to his or her mind is compatible with interpersonal communication and understanding. The book treats these major issues against the background of the author's original metaphysics-panenmentalism.